DAYA TARIK WISATA KEBUN BINATANG KASANG KULIM KABUPATEN KAMPAR - Defitri Eka Sukma; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The number of tourist visits in the Kasang Kulim Zoo increased from year to year but not too significant. Given the opportunity Kasang Kulim Zoo this is the only Zoo in Riau province, the purpose of this study to determine the attractiveness of Kasang Kulim Zoo and to know the management effort in managing the attraction of Kasang kulim Zoo. This research was done in Kasang Kulim Zoo Kampar District. This research uses qualitative methode with descriptive approach by collecting data and information field and explain in the form of description without testing hypothesis or make prediction. Analysis data technic obtained by field observation, interview and literature study in though or in the analysis to achieve the ultimate goal. Based on the research results of existing tourist attraction in the Kasang kulim Zoo are in the category of